1998
DOI: 10.1088/0953-2048/11/9/006
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical properties of (Bi-Pb)SrCaCuO

Abstract: The mechanical properties of (Bi, Pb)SrCaCuO (BSCCO) are examined. Particular attention is paid to the effects of porosity on the elastic modulus, the flexural strength, the hardness and the fracture toughness. A study of the effects of porosity on these properties is crucial in developing a clearer idea of the behaviour of BSCCO conductors in service and is a prerequisite for modelling using, for example, finite element techniques. Experiments are carried out which show the effect of pore volume on the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…Theoretical value of elastic modulus of Bi2223 filaments is estimated as 129GPa for Hs tape, as listed in Table 2. Young's modulus of 103-127GPa measured on Bi2223 filaments is previously reported [6,7]. Relative mass density of Bi2223 filaments of a wire from the same batch of our Ag/Bi2223 tape increases from 80% to 100% after consecutive heat treatments at 800-835 o C [8].…”
Section: Figure1supporting
confidence: 64%
“…Theoretical value of elastic modulus of Bi2223 filaments is estimated as 129GPa for Hs tape, as listed in Table 2. Young's modulus of 103-127GPa measured on Bi2223 filaments is previously reported [6,7]. Relative mass density of Bi2223 filaments of a wire from the same batch of our Ag/Bi2223 tape increases from 80% to 100% after consecutive heat treatments at 800-835 o C [8].…”
Section: Figure1supporting
confidence: 64%
“…This suggests that the lamination is capable of holding the brittle Bi-2223 fractions together and that filament fracture is delayed, at least until the yield strain of the lamination is reached. This reinforcement effect is notable considering the reported mechanical properties of dense Bi-2223 of σ failure,tensile ≈ 100 MPa, E 2223 ≈ 70 GPa, and specificaly ε failure,tensile ≈ 0.14% [69, 70], and also in view of the typical 0.3% – 0.4% strain limits that are commonly observed in Bi-based/Ag-alloy superconductors as discussed in our introduction.…”
Section: Discussionmentioning
confidence: 65%
“…Conventionally, the stress value at this point is usually taken to be the one that causes a 0.20% permanent strain. It's reported that the stress hence, the 95% I (ε) c retention in Ag/Bi -2223 is reversible in the VAMAS tapes up to a 9,17 strain level of 0.4%. .…”
Section: Resultsmentioning
confidence: 99%
“…4, fortunately or unfortunately this is not the case. A subtle residual strain scatter is so results from [2][3][4][5][6][7][8][9][10][11][12][13][14][26][27][28][29][30][31][32] each experiment. Note that the above estimation is a rough one but nonetheless, the achieved σ -ε values from these tests were useful for describing the strain hardening and the pre-compressive force features of this composite wire.…”
mentioning
confidence: 99%